Answer:
![{ \rm{y = \frac{3 \sqrt{x} + 2x}{ {4x}^{2} } }} \\](https://tex.z-dn.net/?f=%7B%20%5Crm%7By%20%3D%20%20%5Cfrac%7B3%20%5Csqrt%7Bx%7D%20%20%2B%202x%7D%7B%20%7B4x%7D%5E%7B2%7D%20%7D%20%7D%7D%20%5C%5C%20)
• We are gonna use the quotient rule
![{ \boxed{ \bf{ \frac{dy}{dx} = \frac{ {\huge{v} } \frac{du}{dx} - { \huge{u}} \frac{dv}{dx} }{ {v}^{2} } }}} \\](https://tex.z-dn.net/?f=%7B%20%5Cboxed%7B%20%5Cbf%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%20%5Cfrac%7B%20%7B%5Chuge%7Bv%7D%20%7D%20%5Cfrac%7Bdu%7D%7Bdx%7D%20%20%20-%20%7B%20%5Chuge%7Bu%7D%7D%20%5Cfrac%7Bdv%7D%7Bdx%7D%20%7D%7B%20%7Bv%7D%5E%7B2%7D%20%7D%20%20%7D%7D%7D%20%5C%5C%20)
- u is (3√x + 2x)
- v is 4x²
- du/dx is 3/2√x
- dv/dx is 8x
• Therefore:
![{ \rm{ \frac{dy}{dx} = \frac{(4 {x}^{2})( \frac{3}{2 \sqrt{x} }) - (3 \sqrt{x} + 2x)(8x) }{16 {x}^{4} } }} \\ \\ { \rm{ \frac{dy}{dx} = \frac{(6 {x}^{2})( {x}^{ - \frac{1}{2} } ) - (24 {x}^{ \frac{3}{2} } + 16 {x}^{2} ) }{16 {x}^{4} } }} \\ \\ { \rm{ \frac{dy}{dx} = \frac{ 6 {x}^{ \frac{3}{2} } - {24x}^{ \frac{3}{2} } - {16x}^{2} }{16 {x}^{4} } }} \\ \\ { \rm{ \frac{dy}{dx} = \frac{ - 18 {x}^{ \frac{3}{2} } - 16 {x}^{2} }{16 {x}^{4} } }} \\ \\ { \rm{ \frac{dy}{dx} = - 2 {x}^{ \frac{3}{2} } (9 + 8 {x}^{ \frac{4}{3} } ) \div 16 {x}^{4} }} \\ \\ { \boxed{ \boxed{ \rm{ \: \: \frac{dy}{dx} = - \frac{8 \sqrt{ {x}^{ \frac{8}{3} }} + 9}{8x {}^{ \frac{8}{3} } } \: \: }}}}](https://tex.z-dn.net/?f=%7B%20%5Crm%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%20%5Cfrac%7B%284%20%7Bx%7D%5E%7B2%7D%29%28%20%5Cfrac%7B3%7D%7B2%20%5Csqrt%7Bx%7D%20%7D%29%20-%20%283%20%5Csqrt%7Bx%7D%20%2B%202x%29%288x%29%20%20%20%7D%7B16%20%7Bx%7D%5E%7B4%7D%20%7D%20%20%7D%7D%20%5C%5C%20%20%5C%5C%20%7B%20%5Crm%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%20%5Cfrac%7B%286%20%7Bx%7D%5E%7B2%7D%29%28%20%7Bx%7D%5E%7B%20-%20%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%20%29%20-%20%2824%20%7Bx%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%20%7D%20%2B%2016%20%7Bx%7D%5E%7B2%7D%20%29%20%7D%7B16%20%7Bx%7D%5E%7B4%7D%20%7D%20%20%7D%7D%20%5C%5C%20%20%5C%5C%20%7B%20%5Crm%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%20%5Cfrac%7B%206%20%7Bx%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%7D%20%20-%20%20%7B24x%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%7D%20%20-%20%20%7B16x%7D%5E%7B2%7D%20%7D%7B16%20%7Bx%7D%5E%7B4%7D%20%7D%20%7D%7D%20%5C%5C%20%20%5C%5C%20%7B%20%5Crm%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%20%5Cfrac%7B%20-%2018%20%7Bx%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%20%7D%20-%2016%20%7Bx%7D%5E%7B2%7D%20%20%7D%7B16%20%7Bx%7D%5E%7B4%7D%20%7D%20%7D%7D%20%5C%5C%20%20%5C%5C%20%7B%20%5Crm%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%20-%202%20%7Bx%7D%5E%7B%20%5Cfrac%7B3%7D%7B2%7D%20%7D%20%289%20%2B%208%20%7Bx%7D%5E%7B%20%5Cfrac%7B4%7D%7B3%7D%20%7D%20%29%20%5Cdiv%2016%20%7Bx%7D%5E%7B4%7D%20%7D%7D%20%5C%5C%20%20%5C%5C%20%7B%20%5Cboxed%7B%20%5Cboxed%7B%20%5Crm%7B%20%5C%3A%20%20%5C%3A%20%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%20%3D%20%20%20-%20%5Cfrac%7B8%20%5Csqrt%7B%20%7Bx%7D%5E%7B%20%5Cfrac%7B8%7D%7B3%7D%20%7D%7D%20%20%2B%209%7D%7B8x%20%7B%7D%5E%7B%20%5Cfrac%7B8%7D%7B3%7D%20%7D%20%7D%20%20%5C%3A%20%20%5C%3A%20%7D%7D%7D%7D)
Answer:
20 bags
Step-by-step explanation:
gift + lunch + (skittles * count) ≤ $21
9.25 + 3.50 + 0.40x ≤ 21
12.75 + 0.40x ≤ 21
0.40x ≤ 8.25
x ≤ 20.625
Answer:
x=-2
Step-by-step explanation:
Hey there!
In order to solve this equation, you need to combine like terms
The equation after combining the x terms and the contants will look like this
10x+3=12x+7
Now you have to take 10x away from both sides
3=2x+7
Now bring all the constants to the left side
3-7=2x
Simplify
-4=2x
divide 2 on both sides to get x by itself
x=-2
So, the answer is x=-2
Answer:
i think it is A sorry if I am worng
Answer:
2 x 2 x 3 x 7
Step-by-step explanation:
2x2=4
4x3=12
12x7=84